Three-stage control architecture for cascaded H-Bridge inverters in large-scale PV systems – Real time simulation validation. (1st November 2018) - Vavilapalli, Sridhar; Umashankar, S.; Sanjeevikumar, P.; Ramachandaramurthy, Vigna K.; Mihet-Popa, Lucian; Fedák, Viliam
Highlights: Decentralized control architecture for a CHB Inverter in PV applications is proposed. Module level MPPT proposed in this work improves the transient response of system. Independent MPPT controls in phase level card provides better efficiency. CHB based PV-STATCOM operation is possible with the controls in master controller. Abstract: In large-scale PV power stations, Cascaded H-Bridge (CHB) inverter based PV power conditioning systems are recommended over a conventional Two-Level Inverter based systems since CHB operates at medium voltage levels and provides better power quality. An insulated-gate bipolar transistor (IGBT) based H-bridge along with the auxiliaries such as DC link capacitors, breakers, contactors, bypass switch, voltage and current transducers is the fundamental power module of a CHB inverter. In this paper, the procedure for selection of components for Basic building block is presented. Due to a higher number of H-Bridge modules in a large-scale system, it is difficult to control the system with a single controller card. In this work, a control architecture for three-phase CHB based PV power conditioning systems is proposed in which the controls are distributed into three different stages. With the proposed control architecture, independent Maximum power point tracking (MPPT) controls of each PV array is carried out at module level itself. Carrying out MPPT controls at module level helps in improving the computational speed and in maintaining modularity. Hardware requirements of individual processor cards also minimized with the proposed control architecture. In this work, functionalities of each controller card namely module level control card, phase-level control card and master controller cards are explained in detail. Detailed interfacing and signal exchange between H-Bridge modules and the other controller cards are also presented. Controller-in-loop simulations are carried out with the help of Real-Time Simulator to validate the functionalities of each controller card. Real-Time simulation results are presented to verify the operation of the system with the proposed control architecture. Performance and dynamic response of MPPT controls for sudden changes in irradiance inputs on PV arrays are studied. Operation of the system during unequal irradiance inputs on the PV arrays is also analyzed. Current sharing between PV Inverter and grid to feed a fixed load for different values of irradiance inputs is explained through the presented results.